(3CNHGQ HZOGO heG LGhQgG ef GdHdGOs - (3GdGdhSj , eMehO TcQj Hf YHO Gddg Hf TgGH GdOjf eMehO GdGdhSj GdMSjfj, CHhGdeYGdj,J (B1342 (3g` s ((3EHQGgje Hf YHOGddg s)
(3ChdgG (B:s
(3GeG HYO aEf af GdJGQjN af eajO dGSjeG hWffG OGQ GdSdGe s
(3BNQgG (B:s
(3hMjK hba HfG Gdbde aj gPG GdeLdO hgh GdChd ef YOI eLdOGJ , YRefG HMhdg JYGdi Cf fHJOF GdeLdO GdKGfj Ydi ef Jhdj HZOGO ef GdMcGe s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B169s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B19 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs